Thinking in times of crisis: how to converse with life? - Guevara-Aristizábal, Juan Felipe; Eschenhagen, María Luisa (Nómadas, 2018)
The authors’ proposal is based on the concept of a civilization crisis over time and through the current civilizational crisis that we are going through which can be viewed in various socioenvironmental problems. Therefore, it is necessary to propose diferent ways of thinking; in our case, the starting point begins with life – either as a scientiic concept or as a form of inhabiting the planet. This will help us inquire the epistemological foundations of scientiic approaches that have contributed to the current crisis, provide alternative ways of thinking about science and experience other traditions, as is it in “sumak kawsay.”